Strain measurement in concrete structure using distributed fiber optic sensing based on Brillouin scattering with single mode fibers embedded in glass fiber reinforcing vinyl ester rod and bonded to steel reinforcing bars - Bremner, Theodore W.; Bao, Xiaoyi; Georgiades, Tasos (My University, 2001)
The strain distribution in a 1.65m long reinforced concrete beam was measured using the distributed fiber optic sensing system developed by Dr. Bao's Fiber Optic Group at the University of New Brunswick (UNB) with center point and two point loading pattern. A spatial resolution of 0.5m was used. Past experience has shown that the bare optical fiber is too fragile to act as a sensor in a reinforced concrete structure. Therefore, in this experiment, two methods of protecting the fibers were incorporated into the concrete beam to increase the fibers' resistance to mechanical damages and prevent chemical reaction from occurring between the fibers and the concrete. The fibers were either embedded in pultruded glass fiber reinforced vinyl ester (GFRP) rods or bonded to the steel reinforcing bars with an epoxy adhesive. The strain at midspan of the beam as measured by the distributed sensing system was compared with the readings of electrical resistance strain (ERS) and mechanical strain (MS) gauges. The experimental results showed that the pultruded GFRP rods effectively protected the fibers, but the strain readings from the GFRP rods did not agree with the strain measurement of the ERS on the steel reinforcing bars due to the possible slippage of the rods in the concrete. However, the fiber bonded to steel reinforcing bars produced more accurate results and confirmed the potential of this technology to accurately measure strain in a reinforced concrete structure. As expected, the fiber with direct contact to the concrete and steel reinforcing bar, can effectively measured the strain under center point or two point loading.
Keywords: Brillouin scattering; Strains and stresses; Remote sensing; Optical fiber detectors